Causes of albuminocytological dissociation and the impact of age-adjusted cerebrospinal fluid protein reference intervals: a retrospective chart review of 2627 samples collected at tertiary care centre - Brooks, John Alexander; McCudden, Christopher; Breiner, Ari; Bourque, Pierre R (Université d'Ottawa | University of Ottawa, 2019)
We set out to test the discriminative power of an age-adjusted upper reference limit for cerebrospinal fluid total protein (CSF-TP) in identifying clinically relevant causes of albuminocytological dissociation (ACD).
Keywords: adult neurology; migraine; neurology; neuromuscular disease